Magnetic field sensors using arrays of electrospun magnetoelectric Janus nanowires. (December 2018) - Bauer, Matthew; Wen, Xiao; Tiwari, Prabal; Arnold, David; Andrew, Jennifer
Abstract The fabrication and characterization of the first magnetoelectric sensors utilizing arrays of Janus magnetoelectric composite nanowires composed of barium titanate and cobalt ferrite are presented. By utilizing magnetoelectric nanowires suspended across electrodes above the substrate, substrate clamping is reduced when compared to layered thin-film architectures; this results in enhanced magnetoelectric coupling. Janus magnetoelectric nanowires are fabricated by sol–gel electrospinning, and their length is controlled through the electrospinning and calcination conditions. Using a directed nanomanufacturing approach, the nanowires are then assembled onto pre-patterned metal electrodes on a silicon substrate using dielectrophoresis. Using this process, functional magnetic field sensors are formed by connecting many nanowires in parallel. The observed magnetic field sensitivity from the parallel array of nanowires is 0.514 ± .027 mV Oe−1 at 1 kHz, which translates to a magnetoelectric coefficient of 514 ± 27 mV cm−1  Oe−1 . Nanowires: magnetoelectric sensors A two-phase barium titanate/cobalt ferrite nanowire-based magnetic sensor offers enhanced performance as compared to thin films. Magnetoelectric devices are attractive for magnetic field sensing, and have so far been mostly based on composite thin films of magnetostrictive and piezoelectric phases. However, the film substrate typically limits the size of the magnetoelectric effect, reducing their sensing performance. Now, a team from University of Florida led by Jennifer S. Andrew fabricated composite barium titanate/cobalt ferrite nanowires by electrospinning and suspended them over electrodes, removing the substrate constraints experienced by thin films. Resultantly, their device displays a high magnetoelectric coefficient of 514 ± 27 mV cm−1   Oe−1. This work demonstrates the potential that one-dimensional materials offer for magnetoelectric based devices including magnetic field sensors.